2008
DOI: 10.1093/cercor/bhm187
|View full text |Cite
|
Sign up to set email alerts
|

Visual Modulation of Neurons in Auditory Cortex

Abstract: Our brain integrates the information provided by the different sensory modalities into a coherent percept, and recent studies suggest that this process is not restricted to higher association areas. Here we evaluate the hypothesis that auditory cortical fields are involved in cross-modal processing by probing individual neurons for audiovisual interactions. We find that visual stimuli modulate auditory processing both at the level of field potentials and single-unit activity and already in primary and secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
440
6
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 486 publications
(509 citation statements)
references
References 94 publications
62
440
6
1
Order By: Relevance
“…In the non-human primate (see also other chapters in this issue), several electrophysiological experiments have similarly revealed audio-visual interactions in the auditory cortex (Ghazanfar et al, 2005;Bizley et al, 2007;Bizley and King, 2008;Cappe et al, 2007b;Kayser et al, 2008) down to the level of A1 (Kayser et al, 2008). These recent results were highly complementary to the pioneer works of Schroeder's laboratory that have revealed the multimodal feature of the monkey auditory belt where both visual and somatosensory responses can be evoked (Schroeder et al, 2001;Schroeder and Foxe, 2002;Fu et al, 2003).…”
Section: Electrophysiological Evidence In the Primary Sensory Areasmentioning
confidence: 78%
See 2 more Smart Citations
“…In the non-human primate (see also other chapters in this issue), several electrophysiological experiments have similarly revealed audio-visual interactions in the auditory cortex (Ghazanfar et al, 2005;Bizley et al, 2007;Bizley and King, 2008;Cappe et al, 2007b;Kayser et al, 2008) down to the level of A1 (Kayser et al, 2008). These recent results were highly complementary to the pioneer works of Schroeder's laboratory that have revealed the multimodal feature of the monkey auditory belt where both visual and somatosensory responses can be evoked (Schroeder et al, 2001;Schroeder and Foxe, 2002;Fu et al, 2003).…”
Section: Electrophysiological Evidence In the Primary Sensory Areasmentioning
confidence: 78%
“…Although somewhat surprising, there is evidence for the existence of multisensory neurons in areas traditionally considered as unisensory, such as the visual cortex (between areas 17 and 18a) in the rat (Barth et al, 1995) and in the auditory cortex of the monkey (Watanabe and Iwai, 1991;Schroeder et al, 2001;Cappe et al, 2007b;Kayser et al, 2008) and of the ferret (Bizley et al, 2007;Bizley and King, 2008). In addition, previous studies have shown the existence of scattered projections of the auditory cortex towards the visual area 18 in the rat and the cat (Miller and Vogt, 1984;Innocenti et al, 1988).…”
Section: Primary Sensory Areas Receive Non-specific Inputsmentioning
confidence: 98%
See 1 more Smart Citation
“…In marmosets, retrograde tracers in A1 also did not produce labeled cells in early visual areas (Cappe and Barone 2005), but the ferret does have a projection from V1 to A1 (Bizley et al 2007). At least some visual responses have been identified in A1 (Kayser et al 2007(Kayser et al , 2008, but these could arise from other sources besides early visual cortex, for example, from thalamic nuclei or multisensory association areas (Musacchia and Schroeder 2009;Smiley and Falchier 2009). …”
Section: Reciprocity Of Visuo-auditory Convergence Pathwaysmentioning
confidence: 95%
“…Area Tpt was not differentiated in that study but was included as part of CPB. Electrode recordings also showed visual responses across these areas in macaque monkeys, but these did not clearly demonstrate a stronger response in lateral compared with medial areas (Kayser et al 2008). In humans, fMRI studies have not always differentiated between auditory areas, but at least some showed more robust visual activation in caudal areas (e.g., van Atteveldt et al 2004;Lehmann et al 2006;Antal et al 2008).…”
Section: Relative Abundance Of Visual Projections To Different Auditomentioning
confidence: 95%